Effects of dip-coating speed and annealing temperature on structural, morphological and optical properties of sol-gel nano-structured TiO2 thin films. Issue 3 (20th August 2014) - Touam, Tahar; Atoui, Mohamed; Hadjoub, Ilhem; Chelouche, Azeddine; Boudine, Boubekeur; Fischer, Alexis; Boudrioua, Azzedine; Doghmane, Abdellaziz
Abstract : We reported material characterization of the nano-structured TiO2 thin films prepared by the sol-gel dip-coating process on glass substrates. The dependence of the structural, morphological and optical properties of the synthesized films on the fabrication parameters such as withdrawal velocity and annealing temperature were investigated by the techniques of X-ray diffraction (XRD), Raman spectroscopy (RS), scanning electron microscopy (SEM), atomic force microscopy (AFM) and UV-visible spectrophotometry. The results indicate that for the TiO2 films annealed at 500 °C there exhibits (1 0 1) XRD peak corresponding to the anatase phase of TiO2 . The latter is consistent with the recorded Raman signal observed at 142 cm -1 ( E g mode) and 391 cm -1 (B 1g mode), respectively. From the analyses made on the SEM micrographs and AFM images, it was revealed that the morphology and surface roughness of the thin films would depend on the withdrawal speed and the heat treatment temperature. The UV-visible spectroscopy analyses show that all the films were transparent in the visible region with an average transmittance of more than 70%. With an increase on the dip-coating speed from 1 cm/min to 3 cm/min, we observed a spectral red shift of the absorption edge from 3.76 eV to 3.71 eV, indicating a decrease in the bandgap energy ( E g ) of the films.